Transforming waiting pauses into opportunity for physical activity: the “Activate your Wait” pilot study - Pasquarella, Cesira; Bizzarro, Assunta; Martini, Rosamaria; Martini, Raffaella; Colucci, Maria Eugenia; Rossi, Deanna; Faetani, Lorenzo; Ghizzoni, Daniele; Seidenari, Chiara; Paroni, Eleonora; Muzzetto, Pierantonio; Romiti, Davide; et al. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Physical activity is recognized as a major health determinant. However, the prevalence of inactivity can be as high as 80% in some adult subpopulations. From the urgent need to implement strategies to fight sedentary behaviour, considering that physical activity is defined as any bodily movement produced by skeletal muscles that require energy expenditure, the pilot study “Activate your Wait” was born. The project aim is to transform waiting pauses during everyday life into opportunities to perform simple stretching and active mobilization exercises. Methods: The pilot study was carried out in 2019 at Terme S. Egidio (Italy). It was divided in three phases: in the pre-intervention a questionnaire was used to evaluate the interest in the project (96 responders); during the intervention, examples of simple exercises that people can do by themselves were illustrated and undertaken by about 120 participants; in the post-intervention an evaluation questionnaire was administered (71 responders). Results: The intervention aroused enthusiastic participation and high approval and resulted in an increase both in willingness to perform exercises during daily waiting pauses (68% vs 94%) and belief in positive results of physical activity on health (74% vs 96%). Conclusions: In a context where the opportunities for physical activity are decreasing and a sedentary lifestyle has reached a high level, this project represents a contribution to the increase in the awareness of the importance of physical activity and the promotion of the culture of movement in the entire population, with an opportunity of easy accessibility in different contexts of life, at all ages.